The Effect of Catfish (Pangasius sp.) Skin Gelatine Addition on the Physical Characteristics of Butterfly Pea Flower (Clitoria ternatea) Jelly Candy - Aditiara, Aqilla; Agustini, Tri Winarni; Wijayanti, Ima (Buletin Oseanografi Marina, 2025)
Gelatine, derived from fish skin collagen hydrolysis.  The hydrocolloid properties of gelatine make it used as a gelling agent in making jelly candy. Butterfly pea flowers contain antioxidants and produce a purplish blue color so that it can be used as a natural coloring in jelly candy. The purpose of this study was to determine the physicochemical characteristics of butterfly pea flower jelly candy with different concentrations of catfish skin gelatine. Catfish skin gelatine is obtained from the process of protein hydrolysis using citric acid solution (C6H8O7). The treatments were different concentrations of 4%, 8%, and 12% catfish skin gelatine in butterfly pea flower jelly candy. The results showed that increasing the concentration of catfish skin gelatine had a significant effect (p<0.05) on texture profile, moisture content, ash content, protein content, antioxidants, and hedonic parameters, but did not have a significant effect (p>0.05) on color parameters. The addition of 8% gelatinee produced the best jelly candy characteristics with a hardness of 3.7 kgf, cohesiveness of 0.41, springiness of 10.9 mm, gumminess of 1.42 kgf, and chewiness of 15.62 kgf.mm-1, fracture force of 3.17 kgf, adhesiveness of -0.3 kgf.mm, moisture content of 15.65%, protein of 9.03%, ash content of 2.26%, IC50 of 85.14 ppm, L*-value of 19.51, a*-value of 0.44, b*-value of 0.63, and hedonic of 7.30<µ<7.76. The addition of gelatine with proper concentration in butterfly pea flower jelly candy produces the best texture, moisture content, ash content, protein content, antioxidants, and hedonic characteristics, but does not affect color.